Design and synthesis of a new near-infrared and large Stokes shift fluorescence probe for NAD(P)H:quinone oxidoreductase 1 detection in living systems. (February 2023) - Wang, Yu; Ma, Ting; Dong, Junqiang
Abstract: NAD(P)H:quinone oxidoreductase 1 (NQO1) is a kind of anti-oxidant enzyme and widely over-expressed in many cancers. Accurate detection of its activity may be applied for early screening certain cancers. In this work, a new near-infrared and large Stokes shift fluorescence probe (HHW-1 ) based on chloro-substituted dicyanoisophorone was designed for NQO1 detection. HHW-1 was constructed through trimethyl lock quinone to pull-push the optical tuable hydroxyl group of chloro-substituted dicyanoisophorone fluorophore. HHW-1 was applied to detect NQO1 with "off-on" fluorescent signal and large Stokes shift (150 nm) in a time-dependent manner, exhibiting a high selectivity and low detection limit (5.6 ng/mL). Moreover, HHW-1 possessed good optical performance to track the change of NQO1 activity in cells caused by dicoumarin (Dic). What' more, HHW-1 was also applied to track NQO1 activity in tumor bearing mice. All taken together, HHW-1 was an excellent indicator for NQO1 detection in living bio-systems, which may be used for early tumor diagnose. Highlights: A new dicyanoisophorone-based NIR fluorescent probe HHW-1 was developed for NQO1 detection. HHW-1 featured a NIR emission triggered by NQO1 with a large Stokes shift (150 nm) . HHW-1 exhibited high sensitivity (LOD∼5.6 ng/mL). HHW-1 was successfully applied to detect NQO1 in living cells and in vivo .